Testicular germ-cell tumours and penile squamous cell carcinoma: Appropriate management makes the difference. Issue 1 (January 2019) - ; Hackl, Monika; Eycken, Elizabeth Van; Henau, Kris; Dimitrova, Nadya; Sekerija, Mario; Dušek, Ladislav; Mägi, Margit; Malila, Nea; Leinonen, Maarit; Velten, Michel; Troussard, Xavier; et al.
Abstract: Germ-cell tumours (GCT) of the testis and penile squamous cell carcinoma (PeSCC) are a rare and a very rare uro-genital cancers, respectively. Both tumours are well defined entities in terms of management, where specific recommendations - in the form of continuously up-to-dated guide lines-are provided. Impact of these tumour is relevant. Testicular GCT affects young, healthy men at the beginning of their adult life. PeSCC affects older men, but a proportion of these patients are young and the personal consequences of the disease may be devastating. Deviation from recommended management may be a reason of a significant prognostic worsening, as proper treatment favourably impacts on these tumours, dramatically on GCT and significantly on PeSCC. RARECAREnet data may permit to analyse how survivals may vary according to geographical areas, histology and age, leading to assume that non-homogeneous health-care resources may impact the cure and definitive outcomes. In support of this hypothesis, some epidemiologic datasets and clinical findings would indicate that survival may improve when appropriate treatments are delivered, linked to a different accessibility to the best health institutions, as a consequence of geographical, cultural and economic barriers. Finally, strong clues based on epidemiological and clinical data support the hypothesis that treatment delivered at reference centres or under the aegis of a qualified multi-institutional network is associated with a better prognosis of patients with these malignancies. The ERN EURACAN represents the best current European effort to answer this clinical need.